Learner strategies for dealing with pronunciation issues in Mandarin. (August 2018) - Jiang, Xiaoli; Cohen, Andrew D.
Abstract: Learners have difficulty with the pronunciation of both consonants, vowels, and tones in Mandarin Chinese. While there are numerous studies which describe these difficulties, there seem to be few studies looking at the strategies that these learners actually use in order to cope with them. This study focused exclusively on oral production and not auditory comprehension, with special emphasis on the strategies that learners reported using in attempting to master pronunciation of Chinese. The study examined reported and actual difficulties in Chinese pronunciation, along with reported and actual pronunciation strategies. The findings showed both consistencies and inconsistencies between students' self-report of difficulties in pronunciation and the errors that they made. Likewise, there were found to be similarities and differences between what the students reported their strategies were for dealing with Chinese pronunciation and the strategies that were reportedly used in the read-aloud task.